2007
DOI: 10.1063/1.2734897
|View full text |Cite
|
Sign up to set email alerts
|

Microwave shielding of transparent and conducting single-walled carbon nanotube films

Abstract: The authors measured the transport properties of single-walled carbon nanotube ͑SWCNT͒ films in the microwave frequency range from 10 MHz to 30 GHz by using the Corbino reflection technique from temperatures of 20-400 K. Based on the real and imaginary parts of the microwave conductivity, they calculated the shielding effectiveness for various film thicknesses. Shielding effectiveness of 43 dB at 10 MHz and 28 dB at 10 GHz are found for films with 90% optical transmittance, which suggests that SWCNT films are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 30 publications
(35 reference statements)
7
133
0
1
Order By: Relevance
“…Moreover, the large values at low frequency are also consistent with those large values reported (M.A. EL Sabbagh et al, 2009b, and H. Xu et al, 2007). It should be noted the curve difference of the real part the permittivity function of the density between Fig.…”
Section: Complex Permittivity Of Cnt Networksupporting
confidence: 80%
“…Moreover, the large values at low frequency are also consistent with those large values reported (M.A. EL Sabbagh et al, 2009b, and H. Xu et al, 2007). It should be noted the curve difference of the real part the permittivity function of the density between Fig.…”
Section: Complex Permittivity Of Cnt Networksupporting
confidence: 80%
“…It is observed that at low frequencies, the real and imaginary parts of the permittivity are the largest. The [5], [12] and [17].…”
Section: B Carbon Nanotube Networkmentioning
confidence: 99%
“…Thin films of conducting single wall carbon nanotube of a thicknesses less than 300 nm on polyethylene terephthalate substrates are good candidate for this application. (Xu et al 2007) introduced an experimental study to characterize the shielding properties of these composite films. Their study is based on measuring the reflection coefficient of a coaxial annular ring resonator placed above the carbon nanotube layer by using a vector network analyzer.…”
Section: Carbon Nanotubes Composites For Rf Absorbing and Shielding Amentioning
confidence: 99%
“…This property makes carbon nanotubes are not suitable for antenna design. However, this high attenuation property is more suitable for other applications which are based on absorbing or attenuating electromagnetic waves like transparent electromagnetic shielding (Xu et al, 2007) and microwave heating in biomedical applications (Mashal et al, 2010). On the other hand, at higher frequency bands in the range above 100 GHz, this attenuation coefficient is decreased and carbon nanotubes can be a good candidate to design low loss antenna structures of much smaller size compared with operating free space wave length (Huang et al 2008& Attiya, 2009).…”
Section: Introductionmentioning
confidence: 99%